Creating community : an action plan for parks and recreation - Adams, Jane H. (Human Kinetics, 2008)
When municipal monies shrink, park and recreation departments look for new ways to develop their operations and budgets. Park and recreation professionals need to learn how to go after their market share so their departments can continue to expand and compete with other community services.